Can Isoflavones Influence Prostate Specific Antigen Serum Levels in Localized Prostate Cancer? A Systematic Review. (16th March 2021) - Ratha, Prasan; Neumann, Thomas; Schmidt, Christian Andreas; Schneidewind, Laila
Abstract: Low risk prostate cancer does not always necessitate aggressive or invasive intervention and is best monitored through active surveillance, but in daily practice a majority of men seek a more proactive approach. Therefore, tertiary chemoprevention is an attractive option for men seeking a way to slow disease progression. Several natural anti-carcinogens have been identified in soy beans, especially isoflavones. Case series have been published, demonstrating a positive influence of isoflavones on PSA serum levels in prostate cancer. Consequently, we decided to perform a systematic review about the effect of isoflavones compared to placebo on PSA levels in localized prostate cancer following the recommendations provided in the Cochrane Handbook of systematic Reviews. On the whole, the primary aim of this review is to summarize the evidence for the use of isoflavones in localized prostate cancer in terms of PSA response. As a result, in all randomized controlled trials identified for this review, isoflavones seem to have no influence on PSA levels in localized prostate cancer. The influence of isoflavones on overall survival in localized prostate cancer remains unclear. Furthermore, isoflavones are interesting substances for further research, for example in lipid metabolism and cholesterol.